Comparing Disaster Medical Records: Insights from a Tabletop Exercise - Ari Prasetyadjati; Arifin; Nanik Setijowati; Suryanto Eko Agung Nugroho; Istan Irmansyah Irsan (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Background: Medical records are crucial for healthcare management during disasters. However, the World Health Organization’s Emergency Medical Team Minimum Data Set (EMT-MDS) is a relatively new standard and remains unfamiliar to many practitioners. In Indonesia, its implementation is further challenged by language barriers, making evaluation against locally adapted documentation formats necessary. Objectives: This study compares the effectiveness of EMT-MDS with a conventional medical record prototype adapted from Indonesian Ministry of Health guidelines. Methods: A quantitative comparative study was conducted using a Table Top Exercise (TTX) simulation. Two simulation teams acting as Type 1 EMT managed 64 randomized cases using either the EMT-MDS or the conventional format. Results: Statistical analysis using Mann-Whitney, McNemar, and Kappa tests showed no significant differences in completion time (p = 0.642) or data completeness (p = 0.980). Wilcoxon One-Sample tests indicated that both systems performed below ideal reference standards. However, EMT-MDS demonstrated better decision-making quality, with higher agreement with scenario keys for patient outcomes (Kappa = 0.848) and coordination assessments (Kappa = 0.968). Conclusion: EMT-MDS better supports accurate decision-making. Therefore, it is recommended for adaptation into the Indonesian EMT documentation system, accompanied by language adjustments and enhanced training for medical personnel.